2016
DOI: 10.1186/s12907-016-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological techniques for the diagnosis of combat-related invasive fungal wound infections

Abstract: BackgroundEffective management of trauma-related invasive fungal wound infections (IFIs) depends on early diagnosis and timely initiation of treatment. We evaluated the utility of routine staining, histochemical stains and frozen section for fungal element identification.MethodsA total of 383 histopathological specimens collected from 66 combat-injured United States military personnel with IFIs were independently reviewed by two pathologists. Both periodic acid-Schiff (PAS) and Gomori methenamine silver (GMS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…New techniques may provide a more rapid diagnosis, but widespread implementation is often hindered by cost and decreased sensitivity or specificity. For example, frozen sections have a positive predictive value of 92% and negative predictive value of 87% when compared to permanent sections (Warkentien et al, 2012;Heaton et al, 2016). Protocols for early screening may provide an alternate avenue to minimize delays between injury, diagnosis, and treatment.…”
Section: Militarymentioning
confidence: 99%
“…New techniques may provide a more rapid diagnosis, but widespread implementation is often hindered by cost and decreased sensitivity or specificity. For example, frozen sections have a positive predictive value of 92% and negative predictive value of 87% when compared to permanent sections (Warkentien et al, 2012;Heaton et al, 2016). Protocols for early screening may provide an alternate avenue to minimize delays between injury, diagnosis, and treatment.…”
Section: Militarymentioning
confidence: 99%
“…Guarner and Brandt and Sundaram et al have shown the difficulties in differentiating colonization and contamination of fungi. 2,10 In our study out of 47 cases of fungal infections, accounting for 0.2% of total histopathological specimens, Phaeohypomycosis constitute a significant proportion of all fungal infections. Phaeohyphomycosis is a collective term for a heterogeneous group of fungal infections caused by dematiaceous fungi and the commonly isolated ones are Exophiala jeanselmei, E. spinifera, and Wangiella dermatitidis.…”
Section: Discussionmentioning
confidence: 67%
“…Consistent with our findings, Heaton et al . [21] evaluated the utility of routine staining, histochemical stains, and frozen section for fungal element identification. They found that results of GMS and PAS were 84% concordant in findings.…”
Section: Discussionmentioning
confidence: 99%